Consumer purchase decision through online shopping among youth society / Nur Azie Azizi Umar - Azizi Umar, Nur Azie (2019)
Nowadays, with the rapid development of Internet technology, online shopping is becoming common and even inevitable among young people in different age. Consumers choose online shopping which is another shopping channel that is more convenient and express than the traditional shopping pattern, and these also attracts more and more people sell products online, from chain store to small individual business. Due to the increasing amount of online sellers, the competition among sellers on the internet will become more and more intense. To stand out, it is useful for researcher to find out what factors affect a potential consumer’s purchasing decision towards online shopping. There were three objectives in this study: (1) To study the factors affecting online shopping among youth society. (2) To understand how the independent variables can influence consumer decision towards online shopping among youth society. (3) To identify ways to help youth society to save their time and cost to purchase goods and services. To this end, a survey was conducted and the 120 questionnaires were distributed among the youth of different level of study. The replies have been analyzed by means of frequency distribution, average and chart analysis. From the results of the survey, time saving, web design quality and trust is significant influence and have moderate positive correlation with consumers’ online purchase decision. While security factor is no significant. Thus, it is suggested that online sellers should pay more attention to attract online consumers and increase their trust towards online stores.